2011
DOI: 10.1128/jb.05099-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Nitrogen Fixation in Azotobacter vinelandii

Abstract: Most biological nitrogen (N 2 ) fixation results from the activity of a molybdenum-dependent nitrogenase, a complex iron-sulfur enzyme found associated with a diversity of bacteria and some methanogenic archaea. Azotobacter vinelandii, an obligate aerobe, fixes nitrogen via the oxygen-sensitive Mo nitrogenase but is also able to fix nitrogen through the activities of genetically distinct alternative forms of nitrogenase designated the Vnf and Anf systems when Mo is limiting. The Vnf system appears to replace M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
121
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 71 publications
12
121
0
Order By: Relevance
“…However, there are other nitrogenase-like sequences encoded in the R. capsulatus genome, which could potentially perform this function (23). In contrast, the increase of vnfENX expression in iron-only conditions in A. vinelandii (14), coupled with the absence of diazotrophic growth in double mutants lacking nifEN and vnfE (13), strongly supports a role for the VnfEN scaffold in FeFe nitrogenase maturation in this organism. Although it is difficult to rationalize the discrepancy between our results and the results observed in A. vinelandii, it is important to emphasize that the strictly aerobic lifestyle of Azotobacter is very different from the facultative anaerobe E. coli, which can only support nitrogen fixation under anaerobic conditions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, there are other nitrogenase-like sequences encoded in the R. capsulatus genome, which could potentially perform this function (23). In contrast, the increase of vnfENX expression in iron-only conditions in A. vinelandii (14), coupled with the absence of diazotrophic growth in double mutants lacking nifEN and vnfE (13), strongly supports a role for the VnfEN scaffold in FeFe nitrogenase maturation in this organism. Although it is difficult to rationalize the discrepancy between our results and the results observed in A. vinelandii, it is important to emphasize that the strictly aerobic lifestyle of Azotobacter is very different from the facultative anaerobe E. coli, which can only support nitrogen fixation under anaerobic conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, some nif genes (e.g., electron transfer components) are specifically adapted to support nitrogenase activity in accordance with the physiological requirements of the host organism. Notably, alternative nitrogenases are only found in species that also encode a molybdenum-dependent nitrogenase (14,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequences were screened for the presence of homologs of nifNXZYQVSUFMWALI 1 I 2 OT and nafY, iscA lrv, and clpX (associated with nif), and manual assignments were verified by using reciprocal BLASTp (see Table S1 in the supplemental material). The composition of gene clusters associated with alternative nitrogenases, which have yet to be identified in a genome that does not also encode nif (5, 6), were not included in phylogenetic and evolutionary analyses, since they appear to utilize components of the nif system to synthesize their active site metalloclusters (19). The FixABCX protein sequences (encoded by fixABCX) from A. vinelandii were used as BLASTp queries in order to determine if the 189 genomes of taxa harboring homologs of nifHDKEB also encoded Fix.…”
Section: Methodsmentioning
confidence: 99%
“…In line with these observations, Northern blot hybridization analyses have indicated differential expression of the nif structural proteins (7), and immunoblotting has shown that the Fe protein occurs in significant excess compared to MoFe protein levels in cultures grown under diazotrophic conditions (2, 7). Moreover, global transcriptional analyses indicate that nifH mRNA accumulates at ϳ3-fold-higher levels than nifD and nifK messages in A. vinelandii grown diazotrophically (4). Because the genes encoding the nitrogenase Fe protein and MoFe protein are cotranscribed in A. vinelandii, a mechanism must exist to control differential nif structural gene transcript abundance.…”
mentioning
confidence: 99%